Fabrication of Li4Ti5O12@CN Composite With Enhanced Rate Properties - Xiao, Hui; Huang, Xiaobing; Ren, Yurong; Ding, Xiang; Zhou, Shibiao (Frontiers in Chemistry, 2019)
Folic acid is first time applied as a carbon-nitrogen precursor to fabricate Li4Ti5O12@CN composites via ball milling Nano-TiO2, Li2CO3 and folic acid with ethanol as solvent, and then followed by heating treatment in argon. XRD, SEM, TEM, XPS, charge-discharge test and EIS were used to evaluate the influence of N-doped carbon coating on its structure, morphologies and electrochemical property. It is demonstrated that compared with pure Li4Ti5O12, carbon-nitrogen coated Li4Ti5O12 composite exhibits superior high-rate performance. It possesses a high discharge capacity of 174, 165 mAh g-1 at 0.5 and 10 C, respectively. Additionally, an initial specific capacity of 96.2% is obtained after 200 cycles at 10C. The remarkable performance might be put down to the N-doped carbon layer providing eﬃciently electron conductive network and nanosized decreasing lithium ion diﬀusion path.